Žitieto na sv. Grigorij dekapolit v r''kopis ms. sl. 307 ot Rum''nskata Akademija - Biljarski Ivan (Zbornik Radova Vizantološkog Instituta, 2013)
The article contains some preliminary observations on a hagiographical text, discovered in a Slavic manuscript from the collection of the Library of Romanian Academy in Bucharest (Ms. sl. 307). The manuscript that was in very poor physical conditions contains a Triodion and Pentecostarion of Nicephorus Kallistos Xantopoulos with full text of the Synodicon of Orthodoxy. After it we find a vita of St Gregory Decapolita. The text is extremely damaged and almost illegible except the title but it is clear that this is not the only known short vita of the holy man. My work hypothesis is that this text could be the only known copy of the Slavic translation of the Vita of St Gregory Decapolita by Ignatius the Deacon.